2019
DOI: 10.17159/wsa/2019.v45.i4.7546
|View full text |Cite
|
Sign up to set email alerts
|

The investigation into the adsorption removal of ammonium by natural and modified zeolites: kinetics, isotherms, and thermodynamics

Abstract: The objectives of this study were to modify Chinese natural zeolite by NaCl and to investigate its suitability as a low-cost clay adsorbent to remove ammonium from aqueous solution. The effect of Ph on ammonium removal was investigated by batch experiments. The findings indicated that Ph has a significant effect on the removal of ammonium by M-Zeo and maximum adsorption occurred at Ph 8. Ion exchange dominated the ammonium adsorption process at neutral Ph, with the order of exchange selectivity being Na+ > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…Moreover, the q ecal form pseudo‐second order plot is correlated with q eexp , expressing the adsorbents’ NH 4 + removal capacity adequately. The results of the present study come in agreement with other studies results, where aluminosilicates were examined for NH 4 + removal, and in all cases, pseudo‐second order kinetics express better this procedure, rendering NH 4 + adsorption on palygorskite samples a chemisorption (Alshameri et al, 2018; Chen et al, 2014; Pan et al, 2019). Moreover, in all cases the rate constant k 2 has negative value, which indicates desorption process (Tan, 2018).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the q ecal form pseudo‐second order plot is correlated with q eexp , expressing the adsorbents’ NH 4 + removal capacity adequately. The results of the present study come in agreement with other studies results, where aluminosilicates were examined for NH 4 + removal, and in all cases, pseudo‐second order kinetics express better this procedure, rendering NH 4 + adsorption on palygorskite samples a chemisorption (Alshameri et al, 2018; Chen et al, 2014; Pan et al, 2019). Moreover, in all cases the rate constant k 2 has negative value, which indicates desorption process (Tan, 2018).…”
Section: Resultssupporting
confidence: 92%
“…Moreover, the enthalpy change ΔH 0 for raw Pal and H‐Pal is negative, to the contrary of Na‐Pal and Ca‐Pal which is positive, revealing the change of reaction's nature from exothermic to endothermic respectively, which can verify the different behavior of Ca‐Pal and Na‐Pal compared to Pal or H‐Pal with temperature variance. The endothermic NH 4 + adsorption on Na‐aluminosilicate materials was also observed in the study of Pan et al (2019), where natural and Na‐zeolite were applied as NH 4 + adsorbents. The change of entropy ΔS 0 is positive only for Ca‐Pal, indicating that the adsorption's randomness is increased compared to raw palygorskite and its other modifications (Anastopoulos & Kyzas, 2016).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Similar results were also recorded by Vu et al (2017) who used biochar. It is likely that at pH values above 9, most of the NH4 + is transformed to NH3(aq) and the electrostatic attraction to clay minerals decreases (Vu et al 2017;Pan et al 2019).…”
Section: Effect Of Phmentioning
confidence: 99%
“…It indicates that the selectivity order of ammonium over other cations on the synthesized zeolite was Ca 2+ > K + > Na + > Mg 2+ . However, several researches showed that ion exchange properties may be different among different zeolites [31,33].…”
Section: Effect Of Coexisting Ionsmentioning
confidence: 99%